Diagnostic usefulness of findings in Doppler sonography for amelanotic melanoma. Issue 9 (27th June 2013) - Kato, Masayuki; Mabuchi, Tomotaka; Yamaoka, Hanako; Ikoma, Norihiro; Tamiya, Shiho; Ozawa, Akira; Taguchi, Masahito; Kuramochi, Akira; Tsuchida, Tetsuya
Abstract: To evaluate the diagnostic usefulness of Doppler sonography for amelanotic melanoma (AM), the correspondence between the findings of dermoscopy and Doppler sonography was investigated in AM in comparison with other hypopigmented tumors. Seven cases with AM and 11 cases with squamous cell carcinoma (SCC), 10 cases with non‐ or hypopigmented basal cell carcinoma (NP‐BCC) and six cases with eccrine poroma (EP) as hypopigmented tumors were investigated. EP is readily recognized by differences from AM and SCC based on a single vertical and non‐torvtuous vessels. NP‐BCC is distinguished from AM based on tortuosity running in a vertical direction. Though findings of tortuosity in vessels and heterogeneity of vessel size are recognized both in AM and SCC: (i) abundant blood flow was recognized more clearly in AM; (ii) total blood flow was more than 40% in most cases of AM (average, 60.9%); and (iii) more vessels which flow into a tumor are found in AM (85.7%). There is no relationship between dermoscopic findings of vessel types and Doppler sonography findings of vessels. In this study, the diagnostic usefulness of the above‐mentioned specific findings in examination may suggest using Doppler sonography for AM as one non‐invasive method.